Wing design for blended-wing-body aircraft - Mat Yazik, Muhamad Hasfanizam; Hameed Sultan, Mohamed Thariq; Ariffin, Ahmad Hamdan (Centre for Advanced Research on Energy, Faculty of Mechanical Engineering, Universiti Teknikal Malaysia Melaka, 2017)
Blended-Wing-Body (BWB) aircraft is a new design pitched as the future of air transport. However, due to the nature of the design that is relatively new, more research has to be made to exploit its advantages. This article studies an initial scaled blended wing body and the effect of different lift distribution on a BWB design. The initial design is adjusted via twist to obtain desired wing loading distribution. Aerodynamic optimization is performed on Selig S5010 aerofoil to further improve the aerodynamic performance of the BWB design.